Evaluating the ISPS Code’s Role in Securing Maritime Trade Amid Regional Conflicts: Insights from Gaza and the Russia-Ukraine War - Suwandi, Muhamad Daffasyarief; Adolf, Huala; Siswandi, Raden Achmad Gusman Catur (Jurnal Hukum Magnum Opus, 2025)
The escalating conflict between Palestine and Israel has significantly impacted the maritime sector. A decline in ship traffic and import-export volumes has disrupted international trade. Houthi attacks on commercial vessels in November 2023 have exacerbated the stability of global maritime trade. The majority of shipping companies have mitigated this risk by diverting their routes to the Cape of Good Hope. This has triggered an increase in shipping costs and insurance premiums, leading to global inflation. A similar situation occurred in the Black Sea during the Russia-Ukraine war in 2022. Ukraine suffered damage to its ports, which led to a drop in wheat exports. However, countries in the region initiated the Black Sea Grain Initiative (BSGI), based on the International Ship and Port Facility Security (ISPS) Code under the International Convention for the Safety of Life at Sea (SOLAS), which successfully helped restore maritime trade. The purpose of this research is to examine the reliability of the ISPS Code in addressing maritime security threats in high-intensity regional conflicts such as the Gaza conflict, by comparing the successful application of the code in the Black Sea during the war. By using the normative juridical research method through a comparative approach, and by using primary legal sources. The results show that the ISPS Code needs improvement, as it lacks contemporaneous and mandatory provisions, making full compliance difficult.